Efeitos da aplicação de medula óssea autóloga na integração de enxertos ósseos homólogos em osso maxilar: avaliação tomográfica e histomorfométrica - Costa, Carlos Eduardo Sorgi da [UNIFESP] (2010)
Aim: The aim of this study was to evaluate the efficacy of homologous block grafts impregnated with autologous bone marrow in horizontal ridge augmentation therapy. Methods: Ten patients with severe ridge volume deficiency in the anterior maxilla were treated with horizontal ridge augmentation. They were randomized into two groups: Five patients using two homologous blocks grafts in the control group and five patients using two homologous blocks grafts impregnated with autologous bone marrow in the experimental group. Hematologists collected 4 mL of bone marrow from the iliac crest of the patients in the experimental group immediately before the surgeries. The blocks were fixated with titanium screws which were employed to obtain rigid fixation and to standartizate reference points for measurement purposes. Computadorized tomography were obtained both preoperatively and 6 months postoperatory which allowed to evaluate the horizontal bone gain. After the healing period of 6 months, the sites were re-opened and the screws were removed. Before implant placement, bone cores were harvested and prepared for histologic and histomorphometric evaluation. Tomographic and histomorphometric measurements are presented as mean + standard deviation. Results: The experimental group showed better tomographic results (P<0.05) in augmenting alveolar thickness, with 4.60 + 1.43 mm ( 118.23 + 56.93 %), compared with the control group, which had 2.15 + 0.47 mm ( 49.91 + 20.24 %) of bone gain. Despite the different results in alveolar thickeness gain between groups, all sites received dental implants. The histomorphometric analysis also showed better results (P<0.05) in the amount of vital mineralized bone in the test group, with 60.7 + 16.18%, compared with the control group, which had 41.44 + 12.50%. Conclusion: The findings of this study suggest that the autologous bone marrow aspirate can increase the regenerative potential of corticocancellous homologous bone graft.